2020
DOI: 10.1016/j.jinf.2020.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and CT imaging features of the COVID-19 pneumonia: Focus on pregnant women and children

Abstract: s u m m a r yBackground: The ongoing outbreak of COVID-19 pneumonia is globally concerning. We aimed to investigate the clinical and CT features in the pregnant women and children with this disease, which have not been well reported. Methods: Clinical and CT data of 59 patients with COVID-19 from January 27 to February 14, 2020 were retrospectively reviewed, including 14 laboratory-confirmed non-pregnant adults, 16 laboratory-confirmed and 25 clinically-diagnosed pregnant women, and 4 laboratory-confirmed chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
213
0
24

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 376 publications
(276 citation statements)
references
References 24 publications
18
213
0
24
Order By: Relevance
“…The symptoms in children with COVID-19 infection have been well described in the literature [9][10][11][12][13][14][15][16][17][18]. Our results are consistent with these previous reports.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The symptoms in children with COVID-19 infection have been well described in the literature [9][10][11][12][13][14][15][16][17][18]. Our results are consistent with these previous reports.…”
Section: Discussionsupporting
confidence: 93%
“…The most common pattern of chest CT is groundglass opacities, followed by local patchy shadowing and then local bilateral patchy shadowing, which is consistent with published data [9][10][11][12][13][14][15][16][17][18]. Our study indicates that chest CT manifested with a predominance of lesions in the subpleural area (41 [95%] of 43) and in lower lung lobes (28 [65%] of 43), especially in the posterior segment (22 [78%] of 28), an area with a relatively dense amount of bronchioles, blood vessels, and alveoli.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For those pregnant women who developed respiratory disease it has been typically non-life-threatening, including pneumonia accompanied by radiological findings of patchy pulmonary infiltrates, ground glass opacities and consolidation. 55 However, in a few cases there have been pregnant women with COVID-19 who have developed severe pneumonia and life-threatening disease. In a report from New York City the infection status of 2 pregnant women was unknown until after delivery when they developed medical complications, were admitted for intensive care and found to have COVID-19 -their infants were negative for the virus.…”
Section: Sars-cov-2 and Covid 19mentioning
confidence: 99%
“…There is no evidence that the virus can be transmitted vertically from the mother to the fetus during pregnancy. This is based on; one study of 9 pregnant women with laboratory-confirmed COVID-19 pneumonia [8];a single case report [9]; a study of 41 pregnant women with confirmed COVID-19 [11]; and a study of 15 pregnant women with COVID-19 [10].…”
Section: Clinical Findingsmentioning
confidence: 99%